Respon Edamame terhadap Pemberian Berbagai Dosis Abu Boiler Kelapa Sawit - Ichwan, Budiyati; Alia, Yulia; Eliyanti, Eliyanti; Zulkarnain, Zulkarnain; Arzita, Arzita; Saputra, Riki Purna (Universitas Batanghari, 2025)
Edamame is a vegetable commodity whose export demand is currently increasing, while its productivity is still below its potential yield. Therefore, to meet export needs, it is necessary to increase productivity by applying boiler ash, which can improve soil fertility and increase the availability of nutrients in the soil. Research aimed at increasing the growth and yield of edamame by applying various doses of boiler ash was conducted at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, at an altitude of 35 meters above sea level. The research used a one-factor Randomized Block Design (RBD) with various doses of boiler ash, consisting of 0 tonha-1; 5 tonha-1; 10 tonha-1; 15 tonha-1; and 20 tonha-1. Each treatment was replicated 5 times. The research results showed that the application of boiler ash was able to increase plant height, the number of young pods per plant, the weight of young pods per plant, the weight of 100 young pods per plant, and edamame production per hectare. A boiler ash dose of 20 tonha-1 resulted in the highest edamame growth and yield.